INDONESIA STRATEGY OF DIPLOMACY IN PROTECTING FEMALE MIGRANT WORKERS (TKW) IN SAUDI ARABIA DURING THE JOKOWI PERIOD - Akis Jasuli (IAIN Bone, 2021)
TKW is an Indonesian resident who meets the prerequisites to work abroad in a business relationship for a certain period. However, there are several problems in the implementation process, such as problems with pre-placement, placement period, and post-placement, which are considered to have many loopholes and are insufficient to protect TKW in Saudi Arabia. This study aims to determine the strategy of Indonesian diplomacy in the protection of Indonesian female workers (Tkw) in Saudi Arabia in the Jokowi era. The study results show that TKW is entitled to protection from their country of origin, namely Indonesia. In addition to the formation of several laws, there are also efforts being made. Such efforts include sending a letter to the King of Saudi Arabia, holding a meeting between the two countries, pleading with Saudi Arabia to protect TKW, who was sentenced to beheading. The request was made not only through letters but also through discussions between the country's two leaders.